Analisa Masuknya Gardu Induk Anggrek dan Rekonfigurasi Jaringan Terhadap Kualitas Tegangan dan Rugi-rugi Daya (Studi Kasus PLN Rayon Kwandang Area Gorontalo) - Muammar Zainuddin; Luthfi Wiraputra (Jurnal Rekayasa Elektrika, 2016)
The quality of the overhead distribution voltage with a length of ± 190,57 kms, in the North Gorontalo district has not met the National Standard for the distribution voltage yet. This causes a voltage drop along the distribution line at 21% during the peak load and the power loss at 219 kW. This paper aims to find the best solution for improving the voltage quality of the distribution line to meet the standard operation voltage for the medium distribution line. The Newton-Raphson method is used to analyze the power flowing along the distribution line and the voltage at their buses. There are three scenarios purposed in this study. The first scenario is to uprate the conductor size (in LK. 01 feeder), the second scenario is to reconfigure the distribution network after the Anggrek Substation was connected to the system and the third scenario is to combine the first and the second scenarios, i.e. uprating conductors and reconfiguring the network. From the three scenarios, the results show that the first scenario has a voltage drop of 19,8%,  the second scenario causes a voltage drop of 8,8% and the third scenario produces the voltage drop of  4,8%. Based on this results, it can be concluded that the third scenario can improve the line voltage much better than the other two scenarios with the power loss of up to 52,4 kW. The Entry of Anggrek Substation must accompany by conductor uprating in line distribution to reach limit voltage standard operation.